Autoimmune blistering skin diseases triggered by COVID-19 vaccinations: An Australian case series - Cowan, Timothy L.; Huang, Cheng; Murrell, Dédée F. (Frontiers in Medicine, 2023)
Autoimmune blistering skin diseases (AIBD) can be induced or flared by a multitude of sources, however, there have been some reports suggesting that this occurrence is due to COVID-19 vaccinations. At a single academic blistering disease centre in Sydney, Australia, a retrospective review was conducted, identifying 59 patients with AIBD seen between February 2021 and November 2022. Secondary to recent COVID-19 vaccination, four patients had induction of bullous pemphigoid, three patients had a flare of pre-existing bullous pemphigoid, one patient had induction of pemphigus, and two patients had a flare of pre-existing pemphigus vulgaris. This adds to our understanding of the role of vaccinations in the activity of AIBD.